2012
DOI: 10.1177/000348941212101103
|View full text |Cite
|
Sign up to set email alerts
|

Hemodynamic Changes during Otolaryngological Office-Based Flexible Endoscopic Procedures

Abstract: These data concur with those of the previous report that found potentially significant hemodynamic changes during office-based procedures. Although preliminary, our findings suggest that it may be wise to monitor vital signs in patients over 50 years of age and patients who are undergoing an esophageal or laser procedure who are at risk for complications that could arise from tachycardia and hypertension.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
4
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 15 publications
1
20
4
1
Order By: Relevance
“…On the contrary, we noted a significantly higher HR and delta value of HR in younger patients (Figure ), opposing a previous study which reported higher HR in older patients . This discrepancy may have resulted from differences in the study subjects: in the population of the previous study, three‐fourths of the patients were greater than 50 years old, whereas our series contained more young patients (64%), potentially magnifying the details of haemodynamic changes in the each of the corresponding population. In addition, compared with younger patients, older patients are more likely to receive cardiovascular medications (35% vs 4%, P <.01, Chi‐square test), some of which (eg alpha and beta blockers) may suppress both the baseline HR and response of perioperative HR elevation and resulted in a lower HR in older patients.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…On the contrary, we noted a significantly higher HR and delta value of HR in younger patients (Figure ), opposing a previous study which reported higher HR in older patients . This discrepancy may have resulted from differences in the study subjects: in the population of the previous study, three‐fourths of the patients were greater than 50 years old, whereas our series contained more young patients (64%), potentially magnifying the details of haemodynamic changes in the each of the corresponding population. In addition, compared with younger patients, older patients are more likely to receive cardiovascular medications (35% vs 4%, P <.01, Chi‐square test), some of which (eg alpha and beta blockers) may suppress both the baseline HR and response of perioperative HR elevation and resulted in a lower HR in older patients.…”
Section: Discussioncontrasting
confidence: 99%
“…This study revealed trends of higher perioperative BP in patients aged ≥50 years, as reported previously . On the contrary, we noted a significantly higher HR and delta value of HR in younger patients (Figure ), opposing a previous study which reported higher HR in older patients .…”
Section: Discussioncontrasting
confidence: 54%
See 2 more Smart Citations
“…As mentioned previously, many studies have shown that unsedated IOLP are relatively safe and well tolerated by patients. Although they are often well tolerated, several studies have shown that statistically significant increases in hemodynamic measures often occur . Our experience does not deviate from the generally accepted view that IOLP are well tolerated and relatively safe.…”
Section: Discussionsupporting
confidence: 48%